NEW SPECTROPHOTOMETRIC METHOD FOR THE DETERMINATION OF MIRTAZAPINE IN PHARMACEUTICAL FORMULATIONS - Rehman, Fozia; Gul, Saima; Hussain, Sajjad; Khan, Sabir [UNESP] (Soc Chilena Quimica, 2016)
A simple extractive spectrophotometric method has been developed for the quantification of mirtazapine. This method is based on the formation of ion-association complex of mirtazapine drug with bromocresol purple dye. The absorbance of the complex was measured at 400 nm. The method was successfully applied to the determination of mirtazapine in their pharmaceutical formulations. The method shows a linear range from 0.2-10 mu g mL(-1) with a molar absorptivity of 1.53 '10(4) L mol(-1) cm(-1). The limit of detection (LOD) and limit of quantification (LOQ) were found to be 0.096 mu g mL-1 and 0.32 mu g mL(-1) respectively. The developed methodology was successfully applied for the determination of mirtazapine in commercial formulation and the percentage recovery was found 99.91 +/- 0.15. The developed methodology promises a feasible, low cost and an efficient method for the routine analysis.
Keywords: Spectrophotometric; ion-association; pharmaceutical formulations